The effects of miR-27a-3p-mediated Smurf2 on bleomycin A5-induced pulmonary fibrosis in rats - Zhang, Jin; Zhang, Jing; Zhang, Qin (Cellular and Molecular Biology, 2020)
This study aimed to explore the effects of miR-27a-3p-mediated Smurf2 on bleomycin A5-induced pulmonary fibrosis in rats. Sixty clean-grade SD rats were made into models of pulmonary fibrosis induced by bleomycin A5. They were randomly divided into the control group (fed as usual), the bleomycin A5 group, and the miR-27a-3p group according to the modeling. Pathological sections and morphological observations were performed on the lung tissues of all rats, and the expression of miR-27a-3p, Smurf2 mRNA, Smurf2 protein, collagen type I (Col I), collagen type III (Col III), and related inflammatory factors in lung tissues were measured. Dual fluorescein detection was performed for miR-27a-3p and Smurf2 in lung tissues. The lung tissue of rats in the bleomycin A5 group showed obvious pathological changes. The degree of pulmonary fibrosis in the miR-27a-3p group was significantly lower than that in the bleomycin A5 group. The expression levels of Smurf2 mRNA, Smurf2 protein, Col I, Col III, and related inflammatory factors in the lung tissue of rats in the control group were notably lower than rats in the bleomycin A5 group and the miR-27a-3p group (levels of those factors in the miR-27a-3p group were lower than the bleomycin A5 group). The expression level of miR-27a-3p in the lung tissue of rats in the control group was significantly higher than that in the bleomycin A5 group and the miR-27a-3p group (miR-27a-3p level in the miR-27a-3p group was significantly higher than in the bleomycin A5 group). Results of dual fluorescein detection demonstrated that Smurf2 was a direct target gene of miR-27a-3p, and the expression of miR-27a-3p negatively associated with Smurf2. Up-regulation of miR-27a-3p expression can effectively improve the disease degree and inflammatory response in rats with pulmonary fibrosis. Its mechanism may be achieved by regulating Smurf2.